THE EFFECT OF BEET (BETA VULGARIS L.) TO SPERMATOZOA MOTILITY OF MOSQUITO COIL-EXPOSED WISTAR RATS - Wulan Widiasmaran; RR Mahayu Dewi Ariani; Farmaditya Eka Putra; Donna Hermawati (Jurnal Kedokteran Diponegoro)
Background : Mosquito coils contain substances such as allethrin, transflurin, pralethrin, cypenothrin and esbiothrin. Alletrin inhalation will pass into the bloodstream. In the liver, the detoxification occurs and produces metabolites that play a role as free radicals. Beets contain betanin, one of the betalalain groups with functions to binding free radicals in the body system. Objective : To investigate the effect beets on spermatozoa motility of wistar rats exposed by mosquito coils. Methods : In this study used post test only control group design. The number of samples was 20 male wistar rats divided into 4 groups. The Control Group (K-) is a group was given standard feed. The Control Group (K+) is only given exposed to mosquito coils. The P1 group was exposed to to mosquito coils and given 8 ml of beet juice. Group P2 was exposed to to mosquito coils and given 16 ml beet juice. The treatment were done for 56 days. Result : The mean value of motility of spermatozoa are group K (-) = 50; group K (+) = 10; group P1 = 29; group P2 = 46. Oneway Anova test showed significant differences in sperm motility in all groups. Post Hoc test showed  significant difference between group K (+) with K (-) (p = <0,001), group K (+) with P1 (p = 0.005), group K (+) with P2 (p = <0,001).  Conclusion : Beet juice can affect the spermatozoa motility of wistar rats exposed by mosquito coils.